Human Rights in the State of the Rule of Law: Between Progressive Law and Positive Law - Setiaji, Mukhamad Luthfan (Lex Scientia Law Review, 2017)
Justice is not only interpreted from what is stated in the law and carried out according to the law, but justice also sees how law is something that lives in society. The perspective of Progressive Law is considered by many to be one of the breakthroughs in the deadlock of our law enforcement which only looks at aspects of law in the book. This paper tries to see how progressive legal views actually are in various human rights enforcement in the context of a rule of law that prioritizes statutory regulations and the principle of legal certainty.